2023
DOI: 10.1002/smll.202207902
|View full text |Cite
|
Sign up to set email alerts
|

Cu Current Collector with Binder‐Free Lithiophilic Nanowire Coating for High Energy Density Lithium Metal Batteries

Abstract: Despite significant efforts to fabricate high energy density (ED) lithium (Li) metal anodes, problems such as dendrite formation and the need for excess Li (leading to low N/P ratios) have hampered Li metal battery (LMB) development. Here, the use of germanium (Ge) nanowires (NWs) directly grown on copper (Cu) substrates (Cu‐Ge) to induce lithiophilicity and subsequently guide Li ions for uniform Li metal deposition/stripping during electrochemical cycling is reported. The NW morphology along with the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…The LFP cells tested at various rates showed that the LFP||3D Cu-LiSn-Li cell demonstrates a higher rate performance and showed a higher capacity when cycled back to 0.2 C (Figure h). The rate capacities of LFP cells with the 3D Cu-LiSn-Li anode were competitive values compared with those of other related works (Table S2). In addition, a lower relaxation voltage can be observed from the galvanostatic curve of the LFP||3D Cu-LiSn-Li (58 mV, Figure i), compared to that of the LFP||Li (68 mV, Figure j).…”
mentioning
confidence: 65%
“…The LFP cells tested at various rates showed that the LFP||3D Cu-LiSn-Li cell demonstrates a higher rate performance and showed a higher capacity when cycled back to 0.2 C (Figure h). The rate capacities of LFP cells with the 3D Cu-LiSn-Li anode were competitive values compared with those of other related works (Table S2). In addition, a lower relaxation voltage can be observed from the galvanostatic curve of the LFP||3D Cu-LiSn-Li (58 mV, Figure i), compared to that of the LFP||Li (68 mV, Figure j).…”
mentioning
confidence: 65%
“…66 Compared with the stable deposition process and initial sedimentation reaction, the energy required increases.Thus, for the same current density, the inducer plays an important role in the overpotential. Cu substrates, 67–69 which possess poor contact affinity with the Li metal, need the nucleation energy Δ E nuc. and are predicted to have the maximum initial deposition overpotential.…”
Section: Discussionmentioning
confidence: 99%
“…Abdul Ahad et al fabricated dense disordered germanium nanowires (Ge NWs) on copper foil using a vapor–solid–solid (VSS) method, which was then directly used as an anode current collector (Cu-Ge) for LMBs. 93 First, the cleaned copper foil was heated to 450 °C. Then, diphenylgermanane (DPG) was injected into it and cooled to obtain the composite current collector (Fig.…”
Section: Irregular Structurementioning
confidence: 99%